Evaluation of Risk Factors Associated with Rotaviral Diarrhoea among Under Five Children in Sylhet Region of Bangladesh (Bangladesh Medical Journal, 2019)
Retrovirus is the major cause of acute severe diarrhea in under five children and contributing 10,000 to 27000 deaths each year in Bangladesh. This cross-sectional study was designed to determine the risk factors associated with Rotaviral among under five children admitted in the Department of Paediatrics, Sylhet MAG Osmani Medical College Hospital, Sylhet and was carried out in the Department of Microbiology during the period from 1st January to 31st December, 2018. Total 184 under five children with acute watery diarrhoea were enrolled in this study by convenient sampling. Stool samples were obtained and assayed for rotavirus antigens by enzyme linked immunosorbent assay (ELISA). Rotaviral antigen was found positive in 86 cases.The Rotavirus infection was found highest in age group of 7 to 12 months (50.56%) and in male (59.30%) children. It was found significantly higher in patients from lower socio-economic condition (64.00%), those who were from rural area (48.75%) and children who were not exclusively breastfed (83.87%). Bottle feeding, lower educational level of mother and overweight of children may serve as predisposing factors of rotavirus disease in these children.Bangladesh Med J. 2019 May; 48 (2): 32-37